PENGARUH PERCEIVED USEFULNESS, PERCEIVED EASE OF USE, DAN KUALITAS LAYANAN TERHADAP KEPUASAN UNTUK MEMBANGUN LOYALITAS - mandasari, cynthia saisaria; Giantari, I Gusti Ayu Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.06.NO.10.TAHUN 2017DO - 10.24843/EEB.2017.v06.i10.p08, 2017)
This study aims to determine the effect of perceived usefulness, perceived ease of use, and quality of service to user satisfaction to build user loyalty GO-JEK applications in the city of Denpasar. The sample used as many as 170 users who have been using the service application GO-JEK at least 3 times in the last 3 months who live in Denpasar with nonprobability sampling technique. This research uses analysis technique PLS (Partial Least Square). The results of the study found that perceived usefulness, and perceived ease of use have a positive and significant effect on user satisfaction, perceived ease of use has a positive and significant effect on perceived usefulness, service quality has a positive but insignificant effect on user satisfaction, service quality has influence Positive and significant to loyalty. Furthermore, user satisfaction has a positive and significant influence on loyalty.